KAJIAN KONTRIBUSI PD. PARKIR DAN PD. PASAR TERHADAP PENDAPATAN ASLI DAERAH KOTA MAKASSAR - Nurmiati Nurmiati; Fina Diana; Lasmana Lasmana (Jurnal Inovasi dan Pelayanan Publik Makassar, 2019)
One of the sources of Makassar City's PAD is sourced from the results of the management of separated regional assets whose management is handed over to the regional companies that have been formed. The Makassar City Government has several regional companies, including the Makassar Raya Regional Parking Company and the Makassar Raya Regional Market Company. This study aims to analyze the potential of PD. Parking and PD. Market in increasing contribution to Regional Original Revenue. The population in this study consisted of managers of PD. Market and PD. Parking as well as objects and users of parking services and markets. The sample selection is done by purposive sampling and accidental sampling. The data collection method is done by observation, interview and documentation while the data analysis used is a contribution analysis and calculation of the potential. The results showed that contribution PD Makassar Raya parking against PAD Makassar City from 2014-2018 is very small, only around 0.024% to 0.097% and on average 0.052%. Contributio PD Makassar Raya's market towards PAD Makassar City from 2014-2018 is very small, only around 0.022% to 0.095% and on average 0.046%. The potential for real acceptance of parking services on the side of a public road based on a survey of parking points can be increased to Rp23,607,531,148, - The potential for real acceptance of market services based on market activity can be increased to Rp. 30,788,432,000. While the optimal potential based on the number of service objects owned by each market unit is Rp. 50,670,426,000.- Some policy recommendations that can be taken such as: The government is asked to set dividend targets based on real potential in the field. Optimization of revenue sourced from PD. Parking by applying a prepaid ticket system. And Creating a parking management auction system for third parties at potential parking locations. It is necessary to make strict regulations from the government for micro economic growth, especially in traditional markets and a feasibility study and development of TPE must be made in several roads in Makassar City.